Johannes August Lattmann. Sozial und liberal im vordemokratischen Hamburger Senat - Guhl, Anton F. (Mäzene für Wissenschaft, 2013)
Johannes August Lattmann played a special role in Hamburg's political culture. As a merchant, he went overseas for two decades and became a partner in the New York trading company Gustav Amsinck & Co. Back in Hamburg he became known by his generous foundations. In 1907 he was one of the donors of the Hamburgische Wissenschaftliche Stiftung (Hamburg Scientific Society) of which he was a member in later years. His election as senator in 1912 was a novelty and was only possible through an alliance of liberal bourgeoisie and social democracy. Lattmann advocated a pluralist coexistence of political positions and confessions, advocated equal suffrage and worked with women protagonists of the women's movement. When he retired from the Senate in 1919, he became manager of the newly established goods trust in order to restore credit lost to the German economy.